Potensi Geodiversity di Sekitar Kawasan Anak Krakatau-Way Kambas, Provinsi Lampung, Sebagai Kandidat Geopark Indonesia - Happy Christin Natalia; Danni Gathot Harbowo; Rinaldi Ikhram (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
The global significance of Krakatau Volcanic Complex and Way Kambas National Park is the best potential areas to be developed as part of a world heritage, particularly as UNESCO Global Geopark. Both of these objects are in the Lampung Province, Indonesia. Soon, it is necessary to identify and make an inventory of key sites that could become the theme of the area. The study of geodiversity and scientific valuation was carried out which referred to the Technical Guidelines for the Assessment of Indonesia Geological Heritage Resources, 2019. Based on these studies and assessments, there are 14 key sites to represent for Geopark Krakatau-Way Kambas themes. These sites are closely related to the evolution of tectonic activity in the Southern Sumatera as well as the dynamics of magmatism and paleovolcanism that have occurred since the Mesozoic which has signification in human history as world heritage.